2022
DOI: 10.1186/s12931-022-01935-9
|View full text |Cite|
|
Sign up to set email alerts
|

Saliva as a non-invasive specimen for COPD assessment

Abstract: Background People with COPD have been reported to bear a distinct airway microbiota from healthy individuals based on bronchoalveolar lavage (BAL) and sputum samples. Unfortunately, the collection of these samples involves relatively invasive procedures and is resource-demanding, limiting its regular use. Non-invasive samples from the upper airways could constitute an interesting alternative, but its relationship with COPD is still underexplored. We examined the merits of saliva to identify the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…This can greatly reduce the interference of confounding factors on the oral flora and ensure the accuracy of the results. The oral bacteria composition of patients with COPD also found the loss of microbiota diversity (23). We also found that CAP group had a lower diversity than healthy controls.…”
Section: Discussionsupporting
confidence: 55%
“…This can greatly reduce the interference of confounding factors on the oral flora and ensure the accuracy of the results. The oral bacteria composition of patients with COPD also found the loss of microbiota diversity (23). We also found that CAP group had a lower diversity than healthy controls.…”
Section: Discussionsupporting
confidence: 55%
“…The oral bacteria composition of patients with COPD also found the loss of microbiota diversity [23]. We also found that CAP group had a lower diversity than healthy controls.…”
Section: Discussionsupporting
confidence: 55%
“…It is a consensus that a negative correlation between disease severity and DOI: 10.1159/000525605 microbiota diversity. Oral bacteria of people with COPD were significantly less diverse (phylogenetic diversityalpha diversity, i.e., within individual diversity) than that of healthy individuals (Mann-Whitney U test, U = 1,275, p = 0.0013) [44]. Interestingly, although no significant differences in the bacterial load of the lung microbiota were found between healthy and COPD patients, the proportion of pathogenic bacteria gradually increased as COPD progressed [45,46].…”
Section: Mechanism Of Oral Microbiota Affecting Copdmentioning
confidence: 99%